Al-Amr bi al-Ma’rūf wa al-Nahy ‘an al-Munkār: Dirāsah fi Arā’i al-‘Ālim HAMKA fī Tafsīr al-Azhar - Murodi, Murodi (Studia Islamika, 2007)
Among Muslims the term amar makruf nahi mungkar (promoting good and preventing vice) is frequently used as a kind of motto for lslamic dakwah. This term has been studied by a good number of Islamic scholars-both classical and contemporary including Ibn Taymiyah in his work amar makruf nahi mungkar. The Mu'tazilites interpreted it to fall within the category of al-Ushul al-Khamsah, (the five principles of belief). In fact, for the Mu'tazilites the doctrine of amar makruf nahi mungkar is held to be a part of faith, to the point that amar makruf nahi mungkar must be enforced when necessary. Because of this, theological groups in the past have resorted to acts of violence in carrying out their duty of amar makruf nahi mungkar, even though this is done only as a last resort when there are no other means.DOI: 10.15408/sdi.v14i2.550